2022
DOI: 10.1037/str0000232
|View full text |Cite
|
Sign up to set email alerts
|

Emotional labor: A two-wave longitudinal person-centered approach.

Abstract: To date, scholars advocate adopting a person-centered approach in the study of emotional labor since it gives a more realistic representation of the use of emotional regulation strategies. More importantly, a crucial yet under-explored issue is the understanding of the stability of latent profiles of emotional labor over time. Accordingly, this research aimed to investigate the stability of these profiles, based on workers' use of surface acting and deep acting, over 3 months. We also analyzed the role of orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
(145 reference statements)
2
4
0
Order By: Relevance
“…Specifically, by using an experimental vignette procedure, we demonstrated that when employees perceive to be dehumanized by their organization, they engage in more surface acting when interacting with others. This finding is consistent with prior studies that have shown a positive correlation between organizational metadehumanization and surface acting (e.g., Nguyen, Cheung, & Stinglhamber, 2021; Nguyen & Stinglhamber, 2021). More importantly, the direction of this causal link is in line with COR theory (Hobfoll, 1989), which suggests that when employees perceive that their resources are threatened by negative events, they strive to preserve and maintain the resources they value, such as social or personal ones (e.g., Hobfoll, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, by using an experimental vignette procedure, we demonstrated that when employees perceive to be dehumanized by their organization, they engage in more surface acting when interacting with others. This finding is consistent with prior studies that have shown a positive correlation between organizational metadehumanization and surface acting (e.g., Nguyen, Cheung, & Stinglhamber, 2021; Nguyen & Stinglhamber, 2021). More importantly, the direction of this causal link is in line with COR theory (Hobfoll, 1989), which suggests that when employees perceive that their resources are threatened by negative events, they strive to preserve and maintain the resources they value, such as social or personal ones (e.g., Hobfoll, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…Most models of emotional labor have suggested that mistreatment in the workplace is an important determinant in the development of surface acting. In particular, recent research has consistently shown that the perception of being dehumanized by the organization (i.e., organizational metadehumanization) engenders the use of surface acting (e.g., Nguyen, Cheung, & Stinglhamber, 2021; Nguyen, Dao, et al, 2021; Nguyen & Stinglhamber, 2020).…”
Section: The Role Of Surface Actingmentioning
confidence: 99%
“…Finally, our field studies reported levels of ODH (Ms = 4.08/3.85/3.91, in Studies 2a/2b/3, respectively), which are comparable to those reported earlier (Ms from 3.07 to 4.14 on a 7-point Likert-type scale with employees originating from a variety of jobs and organizations; Caesens et al, , 2017Demoulin et al, 2021;Nguyen, Besson, & Stinglhamber, 2021;Nguyen, Cheung, & Stinglhamber, 2021;Nguyen, Dao, et al, 2021;Nguyen & Stinglhamber, 2020Stinglhamber et al, 2021;Taskin et al, 2019;Tseng, 2020; and Ms of 3.10 and 3.72 on a 5-point Likert-type scale with employees working in hotels and nurses, respectively; . Those mean scores suggest that dehumanizing experiences are a common phenomenon in organizations.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, research has examined behavioural consequences of ODH. For instance, ODH engenders maladaptive behaviours and reduces adaptive ones (Demoulin et al, 2021; Muhammad & Sarwar, 2021; Nguyen, Cheung, & Stinglhamber, 2021; Nguyen, Dao, et al, 2021; Sarwar et al, 2021; Sarwar & Muhammad, 2021; Stinglhamber et al, 2021; Taskin et al, 2019). Given that the literature on the employee–organization relationship is dominated by social exchange theory (SET; Gibney et al, 2009), this theoretical framework has been used to theoretically explain the link between ODH and work‐related behaviours (Ahmed & Khan, 2016; Muhammad & Sarwar, 2021; Sarwar & Muhammad, 2021; Stinglhamber et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, employee–customer dyadic surveys [ 42 ] can be used to collect data from both employees and customers immediately after their interactions. Latent profile analysis, as used by Nguyen, Cheung, and Stinglhamber [ 86 ], allows researchers to identify distinct emotional labor actor profiles and examine the antecedents and consequences of these profiles. Experience sampling methodology, as used by Scott and Barnes [ 87 ], involves collecting data on emotional labor strategies and their consequences at multiple points throughout the workday.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%